A3.21 TNFα Influences RasGRP1 and RasGRP3 Expression Levels in PBMC, B and T Cells. (25th February 2013) - Golinski, ML; Hiron, M; Guillou, C; Derambure, C; Boyer, O; Le Loët, X; Vittecoq, O; Lequerré, T
Abstract : Background: Rheumatoid arthritis (RA) is the most common inflammatory arthritis. B and T lymphocytes play a central role in the pathophysiology of RA. RasGRP is a member of the CDC25 family of Ras guanyl nucleotide exchange factors. RasGRP1 is expressed in T and B cells whereas RasGRP3 is only expressed in B cells. In previous studies, we have shown that RasGRP3 expression level significantly decreased in Peripheral blood mononuclear cells (PBMC) from RA patients responders to adalimumab after 3 months, leading to the question of TNFα involvement in pathways including RasGRP1 and RasGRP3. Objectives: To study TNFα effects on RasGRP1 and RasGRP3 expression levels in vitro. Methods: We measured by qRT-PCR, RasGRP1 and RasGRP3 expression levels, i) in PBMC from 3 healthy controls (HC), ii) in negative selected B and T cells from PBMC isolated from 3 buffy coat. In each condition, cells were cultured with or without BCR or TCR stimulation for 4 days and TNFα was added for 24 or 48 hours. Immunofluorescence staining was performed to cheque the cell purity and B and T cells stimulation by flow cytometry. To test the functionals effects of RasGRP1 and RasGRP3 overexpression in T and B cells respectively, IL-2 production was measured by ELISA in T-cells, and Elk-1 expression level was measured by qRT-PCR in B cells before and after TNFα stimulation. In addition, TNFα effects on cell proliferation were evaluated by [ 3 H] thymidine incorporation by the B and T cells. Results: In B cells, TNFα induced an increase of RasGRP1 (p < 0.001) and RasGRP3 (p < 0.001) expression levels in absence of BCR stimulation. In the same way, in T cells, TNFα induced an increase of RasGRP1 (p < 0.001) and RasGRP3 (p < 0.001) expression levels in absence of TCR stimulation. Furthermore, TNFα induced a significantly increase of IL-2 production (p < 0.05) in unstimulated T cells and of Elk-1 expression level (p < 0.01) in unstimulated B cells. However, TNFα have no effects on B and T cells proliferation. Conclusions: This study suggests the RasGRP1 and RasGRP3 regulation by TNFα, independently of B and T cells stimulation. The increasing of RasGRP3 and RasGRP1 in B and T cells specifically via TNFα binding on its receptors could promote the activation and proliferation of B and T cells by an independent antigen pathway. This second pathway could explain the maintenance of B and T cells activation.